2008
DOI: 10.1021/jm800961g
|View full text |Cite
|
Sign up to set email alerts
|

Antagonists of the Human A2A Adenosine Receptor. 4. Design, Synthesis, and Preclinical Evaluation of 7-Aryltriazolo[4,5-d]pyrimidines

Abstract: Antagonism of the human A(2A) receptor has been implicated as a point of therapeutic intervention in the alleviation of the symptoms associated with Parkinson's disease. This is thought to occur, at least in part, by increasing the sensitivity of the dopaminergic neurons to the residual, depleted levels of striatal dopamine. We herein describe a novel series of functionalized triazolo[4,5-d]pyrimidine derivatives that display functional antagonism of the A(2A) receptor. Optimization of these compounds has resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 38 publications
2
68
0
1
Order By: Relevance
“…Drugs commonly used in PD treatment are known to counteract the catalepsy induced by haloperidol or reserpine (for review see Duty and Jenner 2011). Moreover, specifically, the catalepsy test induced by haloperidol is useful to underline the pharmacokinetic differences of the compounds tested (Gillespie et al 2009;Neustadt et al 2007;Pinna et al 2005;Weiss et al 2003).…”
Section: Effect Of a 2a Receptor Antagonists On Akinesia Bradykinesimentioning
confidence: 99%
See 1 more Smart Citation
“…Drugs commonly used in PD treatment are known to counteract the catalepsy induced by haloperidol or reserpine (for review see Duty and Jenner 2011). Moreover, specifically, the catalepsy test induced by haloperidol is useful to underline the pharmacokinetic differences of the compounds tested (Gillespie et al 2009;Neustadt et al 2007;Pinna et al 2005;Weiss et al 2003).…”
Section: Effect Of a 2a Receptor Antagonists On Akinesia Bradykinesimentioning
confidence: 99%
“…7.2) (Drabczyńska et al 2011;Gillespie et al 2009;Hodgson et al 2009;Jones et al 2013;Kanda et al 1994;Mandhane et al 1997;Pinna et al 2005;Shiozaki et al 1999;Shook et al 2010Shook et al , 2013Stasi et al 2006;Villanueva-Toledo 2003;Wardas et al 2003;Weiss et al 2003). Furthermore, the co-administration of several A.…”
Section: Effect Of a 2a Receptor Antagonists On Akinesia Bradykinesimentioning
confidence: 99%
“…The presence of a pyrimidine base in cytosine, uracil and thymine, which are these essential building blocks of nucleicacids (DNA and RNA) is one of the possible reasons for their activities [4]. Condensed pyrimidine derivatives have been reported as antimicrobial [5], analgesic, antiviral, antiinflammatory [6], anti-HIV [7], antitubercular [8], antitumor [9], antineoplastic [10], antimalarial [11], diuretic [12], cardiovascular [13] agents and hypnotic drugs for the nervous system [14], calcium-sensing receptor antagonists [15] and also for antagonists of the human A2 A adenosine receptor [16]. In medicinal chemistry pyrimidine derivatives have been well known for their the rapeutic applications.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Recent studies of biological activity mechanisms showed that 8-azapurines act as inhibitors of certain enzymesadenosine deaminase, phosphodiesterase, 6-8 as well as adenosine receptor antagonists. [9][10][11] Another type of azoloazines, [1,2,4]triazolo[1,5-a]-pyrimidines, have also shown various biological activity, primarily as antiviral agents. [12][13][14][15][16] The combination of both aforementioned azoloazine moieties in a single molecular structure has been once reported in the literature, 17 but the compound itself has not been characterized.…”
mentioning
confidence: 99%
“…H NMR spectrum, δ, ppm (J, Hz):10.37 (1Н, d, J = 1.6, Н-5); 9.65 (1Н, d, J = 2.0, Н-7) 13. C NMR spectrum, δ, ppm: 151.7; 148.0; 137.2; 135.7; 127.8; 111.7; 107.5; 106.2.…”
mentioning
confidence: 99%